Effectiveness of health coaching nursing education based on the precede-proceed model theory on medication compliance of TB Patients - Anna Nur Hikmawati; RR.Viantika Kusumasari; Fitri Dian Kurniati (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2026)
Background: Tuberculosis is a contagious infectious disease where its control efforts are one of the world's targets, namely the Sustainable Development Goals (SDGs). Compliance with taking medication in pulmonary TB patients is an obstacle often faced by patients because they have to take medication continuously until the specified time, however in Indonesia there are still many cases of drop out for various reasons such as drug side effects, level of knowledge, habits, lack of family support, environment, socio-economic and health education strategies. The education provided is still one-way and has not touched on psychological, social, and motivational aspects, even though patients have the potential to act as facilitators of behavior change. Objectives: The purpose of this study is to determine the development of health coaching nursing education based on the precede-proceed model theory on medication adherence for TB patients in the Pleret Bantul DIY Community Health Center Working Area. Methods: This research design is quasi- experimental with Non Equivalent Control Group approach. The number of samples in this study refers to Non Probability Sampling type of total sampling amounting to 32, which are divided into 2 intervention and control group of 16 respondents each. The d ata analysis of this study used the Wilcoxon Signed Rank Test and Mann-Withney. Instrument for medication adherence was measured using the Medication Morisky Adherence Scale (MMAS-8). Results: The results showed a significant difference between the control group and the intervention group after health coaching nursing education based on the precede-proceed model theory with a value of p= 0.049 < 0,05. Conclusions: It was concluded that health coaching nursing education based on the precede-proceed model theory influenced medication adherence of TB patients in the Pleret Bantul DIY Community Health Center Work Area